A Systematic Review of Educational Strategies for Enhancing Creativity in Architecture Design Studios - Kwame Sarfo Aboagye Mensah; Prince Osei Adjei; Justice Offei-Nketiah (Journal of Research in Education and Pedagogy, 2026)
This systematic literature review examines educational strategies for enhancing creativity in architectural design studios, synthesizing findings from 24 peer-reviewed studies published between 2015 and 2025. Architectural education has long positioned the design studio as the ideal environment for fostering creativity. However, the increasing integration of digital tools, diverse pedagogical frameworks, and new models of collaboration has reshaped both opportunities and challenges for cultivating innovative thinking. The review highlights a range of pedagogical approaches, such as design thinking models, technology-enhanced learning, experiential and “learning by doing” approaches, and collaborative methods that encourage peer-to-peer and interdisciplinary engagement. Key findings indicate that hybrid models blending structured frameworks with open-ended exploration effectively support the development of creative skills, while the use of digital tools promotes innovation but also risks restricting the design thinking of students if applied uncritically. One critical issue the review highlights concerns the assessment of creativity: despite growing interest in the evaluation of creativity, assessment practices remain inconsistent. Another critical issue the review highlights is the tension between technology and human agency, revealing a need for more balanced pedagogical approaches that value both digital innovation and human-centred exploration. Limitations of the study include the exclusion of potentially relevant studies because of the scope of the database search, a geographical bias toward Western contexts, and a scarcity of longitudinal studies on the sustained impact of creativity-focused strategies on architecture students. The study concludes by underscoring the importance of context-sensitive strategies that harmonize structure and freedom, tradition and innovation, and individual and collaborative learning. By addressing these challenges, architectural educators can better equip students to meet the evolving demands of the architecture profession.